Anisotropic hygro-expansion in hydrogel fibers owing to uniting 3D electrowriting and supramolecular polymer assembly - Wu, Dan Jing; Vonk, Niels H.; Lamers, Brigitte A.G.; Castilho, Miguel; Malda, Jos; Hoefnagels, Johan P.M.; Dankers, Patricia Y.W. (Elsevier Limited, 2020)
Melt electrowriting (MEW) is mostly applied to print complex three-dimensional (3D) structures using traditional, relatively hydrophobic polymers, such as polycaprolactone. Here, we 3D printed a supramolecular hydrophilic polymer into a solid micrometer-sized fiber structure, solely held together via non-covalent interactions. Interestingly, the solid fibers showed anisotropic swelling in a humid environment as demonstrated by the longitudinal and transverse surface strain determined using a novel global digital height correlation algorithm. This anisotropy in swelling is proposed to originate from a shear-induced orientation of crystals packed into lamellae as shown with small-angle x-ray scattering measurements. The MEW fibers were dried after swelling to study structural differences. Remarkably, no differences in nano-structural conformation in the micrometer-sized fibers was observed after swelling and subsequent drying. In conclusion, a free-standing supramolecular polymer-based hydrogel scaffold, displaying anisotropic hygro-expansion, is shown to be produced using MEW. This unique combination of 3D printing, via a top-down approach, and supramolecular polymer chemistry, via a bottom-up approach, provides new ways to introduce anisotropy and hierarchy in aqueous supramolecular systems. This will open the door towards even more complex hierarchical structures with unprecedented properties.
Keywords: Additive manufacturing; Hydrogel; Hygro-expansion; Melt electrowriting; Supramolecular polymer; General Physics and Astronomy; Organic Chemistry; Polymers and Plastics; Materials Chemistry